Logistics education for business management students: a learningdoing and service-learning approach - Cano, Jose Alejandro; Ayala, Carlos (Opción, 2020)
This article develops a teaching methodology in logistics for students of business administration programs to solve real problems in companies and integrate the knowledge acquired in logistics management courses. The methodology integrates project management tools with the support of MSExcel and promotes the elaboration of managerial reports according to the requirements of working environments. The methodology generates high satisfaction in the students, to the extent that it allows them to know in depth the logistic system of a company, identifies opportunities for improvement and proposes solutions based on technical and economic aspects. Likewise, the methodology allows the students to have contact with the directives of a real company and supports the improvement of logistics processes based on qualitative and quantitative information Abtrac Se desarrolla una metodología de enseñanza en logística para estudiantes de programas de administración de empresas para resolver problemas reales en empresas e integrar los conocimientos adquiridos en cursos de gestión logística. La metodología integra herramientas de gestión de proyectos con el soporte de MSExcel. Promueve la elaboración de informes gerenciales conforme con los requisitos de los entornos de trabajo. La metodología genera una gran satisfacción en los estudiantes, en la medida en que les permite conocer en profundidad el sistema logístico de una empresa, identifica oportunidades de mejora y propone soluciones basadas en aspectos técnicos y económicos. Asimismo, permite a los estudiantes tener contacto con las directivas de una empresa real y apoya la mejora de los procesos logísticos basados en información cualitativa y cuantitativa.